2007
DOI: 10.1208/pt0804088
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of matrix-based controlled release tablets of diclofenac sodium and chondroitin sulphate

Abstract: The purpose of the present study was to develop and characterize an oral controlled release drug delivery system for concomitant administration of diclofenac sodium (DS) and chondroitin sulfate (CS). A hydrophilic matrix-based tablet using different concentrations of hydroxypropylmethylcellulose (HPMC) was developed using wet granulation technique to contain 100 mg of DS and 400 mg of CS. Formulations prepared were evaluated for the release of DS and CS over a period of 9 hours in pH 6.8 phosphate buffer using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 37 publications
(16 reference statements)
0
37
0
Order By: Relevance
“…The rate of drug release in this model is controlled by the velocity and position of the front dividing the glassy and rubbery portion of the polymer. Various drug delivery system can be modelled with Korsmeyer-Peppas kinetic model, for example the release of chondroitin sulphate from the hydrophilic HPMC tablets [41], and theophylline released from wax matrix granules [42]. Overall, the Korsmeyer-Peppas model suggests that biological fluids induce swelling of coating layers and gelatin, channels are formed, which allow sCT to be released from minispheres.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of drug release in this model is controlled by the velocity and position of the front dividing the glassy and rubbery portion of the polymer. Various drug delivery system can be modelled with Korsmeyer-Peppas kinetic model, for example the release of chondroitin sulphate from the hydrophilic HPMC tablets [41], and theophylline released from wax matrix granules [42]. Overall, the Korsmeyer-Peppas model suggests that biological fluids induce swelling of coating layers and gelatin, channels are formed, which allow sCT to be released from minispheres.…”
Section: Discussionmentioning
confidence: 99%
“…According to the resultant kinetic parameters (Table I), all release profiles were satisfactorily fitted to the power law equation using appropriate n values (R 2 ≥0.98). The value of n from the free-resin matrices was 0.569, indicating an anomalous transport corresponding to drug diffusion in the hydrated matrix and the polymer erosion (22,23). However, the matrices containing either resin exhibited a trend of decreasing n values, i.e., from 0.569 to 0.227 for Dow88 and from 0.569 to 0.410 for Am64, Fig.…”
Section: Drug Release From Matrices In Deionized Watermentioning
confidence: 93%
“…This result confirms that the release of EN and MN tablets prepared with PAA-Cys were similar to each other. 19) In addition, the similarity factor between PAA tablets was found to be 68.180. The similarity study results confirmed that the presence of EN or MN did not affect the release profile of the drug from the formulations.…”
Section: )mentioning
confidence: 97%